(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Setiawan A, Monik DT, Charles Y, Lestari ER, Ruciyansah Y, Anwar Z. 2021. An assessment of Sumatran elephant presences (Elephas maximus sumatranus) in Kotaagung Utara (Lampung, Indonesia) as a potential tourism attraction. Biodiversitas 22: 5397-5407. Kesatuan Pengelolaan Hutan (KPH) Kotaagung Utara is a region of approximately 56.02 ha, consisting of 8.82% forest cover and 91.18% non-forest cover. This region has a high diversity of flora and fauna and has potential as a tourist destination with various and unique biophysical attractions. One of the special features of this location is the presence of Sumatran elephants [Elephas maximus sumatranus (Temminck, 1847)]. Wild elephants in KPH are a tourism potential that can be developed to become a tourism attraction. The objectives of this research were to find out the elephant home ranges and the right window of time to observe the Sumatran elephants and assess safety, security, and convenience considerations for visitors to observe wild elephants. The method used in the research was an observation, and the results were qualitative data. The data collection’s elephants movement through the use of GPS Collar from 2017-2020. The study identified that there are 16 wild elephants known as the Bunga group. The elephants can be observed from 7:30 to 12:00 am or 3:00 to 6:00 pm, with a duration of 3 hours per day. Steps can be taken to increase visitor’s safety, security and convenience with the building of a treehouse, evacuation route, use of binoculars, and Personal Protective Equipment (PPE).